Step-like and first-order characters of Tb0.2Pr0.8(Fe0.4Co0.6)1.93 with low interstitial carbon content. (August 2015) - Huang, J.W.; Xia, Z.C.; Cheng, G.; Shi, L.R.; Jin, Z.; Chen, B.R.; Shang, C.; Wei, M.
Abstract: In this study we report detailed magnetic property of the 4 f -3 d pseudo-quaternary Tb0.2 Pr0.8 (Fe0.4 Co0.6 )1.88 C0.05 compound by detailed magnetization measurements. Very sharp magnetization jumps across the antiferromagnetic–ferromagnetic transition are observed below 3.0 K, and the number of jump-like transitions increases with decreasing temperature. The time-dependent magnetic relaxation, field sweep rate and cooling field dependence of magnetization jumps resemble the martensitic scenario. The number and occurrence of magnetization jumps are mainly determined by the competitions between the thermal fluctuation energy, elastic energy and Zeeman energy, and the field-induced antiferromagnetic to ferromagnetic phase transition at low temperatures is of first-order in nature. Graphical abstract: Magnetization jumps observed in the C15 Laves phase compound Tb0.2 Pr0.8 (Fe0.4 Co0.6 )1.88 C0.05 . Highlights: We find another kind of Laves phase compound showing magnetization jumps. The number of jumps increases with deceasing temperature below 3.0 K. Ac susceptibility and time-evolution data indicate the existence of a glassy state. Sweep rate and cooling field dependent data resemble the martensitic scenario. Field-induced antiferromagnetic to ferromagnetic transition is of first order.